MATERNAL ROLE ATTAINMENT AND SELF CARE BEHAVIOR THROUGH SOCIAL SUPPORT RELATED HEALTH STATUS OF PREGNANT FEMALE OFFENDER IN CORRECTIONAL INSTITUTION - Lueangbutsarakham, Nualjan; Silapasuwan, Pimpan; Sujirarut, Dusit; Sirisutthidacha, Warissara (Journal of Public Health Nursing, 2019)
The pregnancy of a female prisoner is a difficult condition, and it may affect the process and outcome of pregnancy. The purpose of this descriptive study was to investigate the relationship between maternal role, attainment, self care behaviours, social support and health status of women in prison during pregnancy. The sample was pregnant female who were 18 years of age or older. Data were collected from the structured interview. There were 36 pregnant female in the correctional institution located in the central region. Data were analyzed using Simple Logistic Regression. Maternal roles and social support was at a high level 50%, it was found that 66.67% increased weight during pregnancy. Fetus health status was normal. The mental health of pregnant inmates was at moderate level (47.22%). Female inmates with separated status or divorces increased risk of mental health problems at 9.23 times higher (95% CI = 1.02-83.33). Low universal self care behavior increased risk of mental health problem at 8.56 times(95%CI= 1.53-47.96). Therefore, The research suggests that the mental health should be promoted by increasing family ties.